1988
DOI: 10.1111/j.1365-2621.1988.tb07859.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Protein‐Bound Riboflavin and Free Riboflavin

Abstract: Assay of antioxidizing actionWe studied the antioxidant effects of protein-bound riboflavin and free riboflavin using methyl linoleate in a water system in the dark. The protein-bound riboflavin inhibited the formation of hydroperoxides. After exposure to light, the protein lost its antioxidant effect, which suggested that it was not the protein-bound riboflavin but the riboflavin itself that had the antioxidant effect. These results showed that riboflavin inhibited the formation of hydroperoxides, which sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Riboflavin is also known to possess antioxidant activity both in free form and bound form. Its addition to the fortified beverage might have also contributed to antioxidant activity (Toyosaki & Mineshita, 1988). The TFC of the fortified beverages is main aspect of this research work.…”
Section: Resultsmentioning
confidence: 99%
“…Riboflavin is also known to possess antioxidant activity both in free form and bound form. Its addition to the fortified beverage might have also contributed to antioxidant activity (Toyosaki & Mineshita, 1988). The TFC of the fortified beverages is main aspect of this research work.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated the accumulation of LPO products in the liver (Taniguchi and Hara 1983), lenses (Bates 1991) and erythrocytes (Levin et al 1990) in riboflavin-deficient rats, which indicated a poor antioxidant defense caused by riboflavin deficiency. In vitro studies also indicated that riboflavin was shown to inhibit the formation of hydroperoxides (such as H 2 O 2 and ROOH) (Toyosaki and Mineshita 1988). The mechanism may be that riboflavin can quench free radicals through its reversion from reduced form to oxidized form (Toyosaki 1992).…”
Section: Discussionmentioning
confidence: 96%
“…They suggested that the antimutagenic effect of riboflavin can, at least in part, result from its direct scavenging activity on free radicals produced by mutagens. In vitro studies have also indicated that riboflavin itself has an antioxidant nature, independent of its action as the GR coenzyme ( 47 ) . The suggested mechanism could be the deactivation of hydroperoxide through the reversion of riboflavin from the reduced form (dihydroriboflavin) to the oxidised form (Fig.…”
Section: Effect Of Riboflavin Status On Lipid Peroxidationmentioning
confidence: 99%